ANALISIS PROFITABILITAS PADA PT. SADARIAH DI SAMARINDA - Catur Kumala Dewi, Bunga Sara A Simbolon Ivana Nina Esterlin Barus2 (EKONOMIA, 2021)
This study was conducted to determine whether the increase or decrease in profitability ratios measured by Net Profit Margin (NPM), Return On Investment (ROI), and Return On Equity (ROE) in 2015 to 2017.The analysis used in this study is a comparative descriptive analysis using several analytical tools in the form of net profit margin (NPM), return on investment (ROI), and return on equity (ROE) and then will be seen whether there is an increase or decrease in 2015- 2016 and 2016-2017, then compared with industry standards profitability ratios.Based on the results of the analysis it is known that the profitability ratio of PT. Sadariah as measured by Net Profit Margin (NPM) in 2016 decreased compared to 2015 then in 2017 it increased compared to 2016. The profitability ratio as measured by Return on Investment (ROI) in 2016 decreased compared to with 2015, then in 2017 there was an increase compared to 2016. The profitability ratio measured by Return On Equity (ROE) in 2016 decreased when compared to 2015, in 2017 it increased when compared to 2016.Ratio profitability of PT. Sadariah as measured by Net Profit Margin (NPM) is above industry standards in 2015 and 2017, while in 2016 it was below industry standards. Profitability ratio of PT. Sadariah as measured by Return On Investment (ROI) is below industry standards during 2015-2017. Profitability ratio of PT. Sadariah as measured by Return On Equity (ROE) is below industry standards during 2015-2017.